Fônons em arsenatos e molibdatos de terras-raras - Oliveira, Glaydson Francisco Barros de (2012)
The Raman spectroscopy technique was used to investigate the room-temperature phonon characteristics of two series of single crystals containing rare-earth elements: (i) the rare-eartharsenates (REAsO4), RE=Sm, Eu, Gd, Tb, Dy, Ho, Tm, Yb, and Lu) and (ii) the rare-earth molybdates (RE2(MoO4)3). For the REAsO4(RE=Sm, Eu, Gd, Tb, Dy, Ho, Tm, Yb, and Lu)series the Raman data were interpreted in a systematic manner based on the known tetragonal zircon structure of these compounds, and assignments and correlations were made for the observed bands. We found that the wavenumbers of the internal modes of the AsO4 tetrahedron increased with increasing atomic number. This increase seems to be correlated to the contraction of the RE–O bond length. For three out of four lattice wavenumbers observed, this tendency was not nearly so marked as in the case of the internal mode wavenumber. For the RE2(MoO4)3(RE = Sm, Eu, Gd and Tb) series the Raman spectra exhibit fewer bands than those predicted by the group theory analysis. Due to the large band overlap, correct assignment was given only to the n1 and n3 modes of the MoO4tetrahedra. We observe that the vibrations from tetrahedra II and III are degenerated. The slightly increase of the frequency of the modes n1 and n3 as RE goes from Sm to Tb is likely to be related to the contraction of the orthorhombic cell. We also recorded the Raman spectra of REGd((MoO4)3) (RE = Sm, Er and Tb). No changes were observed. However, when Mo is partially substituted by W, an extra high-frequency mode appears in the Raman spectrum.